Anjum Hasan’s The Cosmopolitans: A Critique of a Cosmopolitan Woman - Islam, Rama (SCHOLARS: Journal of Arts & Humanities, 2022)
Anjum Hasan is a novelist, short story writer, poet and editor. Her third novel The Cosmopolitans (2015) deals with modern life of a cosmopolitan woman named Qayenaat who lives in a cosmopolitan city Bangalore. In cosmopolitanism, a person is free from the local or national bias and becomes a citizen on a global scale. This paper focuses on a sophisticated, fashionable, stylish and cultured woman who is a part of the cosmopolitan world. She is familiar with globalisation, Europeanisation and social process of transformation within the nation and beyond specific societies and cultures – the woman crosses the symbolic boundaries of national communities in India. The novel questions the place of art in modern life and portrays a lonely woman who is at odds with the world. As a cosmopolitan woman, she likes to work outside home and travels freely to different places. Concerned about commercialisation of art and culture and cosmopolitan citizens, she lives lonely in her father’s house, and leads her life as a freelance editor and writer. Thus, the main objective of the study is to explore unconventionality and nomadic life of Qayenaat, who has failed as an artist in her life.